2016
DOI: 10.1371/journal.pmed.1002197
|View full text |Cite
|
Sign up to set email alerts
|

Histological Transformation and Progression in Follicular Lymphoma: A Clonal Evolution Study

Abstract: BackgroundFollicular lymphoma (FL) is an indolent, yet incurable B cell malignancy. A subset of patients experience an increased mortality rate driven by two distinct clinical end points: histological transformation and early progression after immunochemotherapy. The nature of tumor clonal dynamics leading to these clinical end points is poorly understood, and previously determined genetic alterations do not explain the majority of transformed cases or accurately predict early progressive disease. We contend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
207
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 209 publications
(225 citation statements)
references
References 43 publications
16
207
0
2
Order By: Relevance
“…We used the Mb1-cre for deletion of Crebbp at an early stage of B-cell development because BCL2 translocation in human lymphoma is thought to be acquired as a byproduct of faulty VDJ recombination in pre-or pro-B cells. 36 We observed that CREBBP mutations occur as an early secondary event in FL, 14 which has been validated in subsequent studies, 12 and we therefore speculate that this may also occur at an early stage of B-cell development. Inactivation of Crebbp was associated with marked reductions in the frequencies of multiple B-cell subsets in both young and adult mice, in line with prior observations that loss of Crebbp with a Cd19-cre resulted in ;50% loss in peripheral B cells.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We used the Mb1-cre for deletion of Crebbp at an early stage of B-cell development because BCL2 translocation in human lymphoma is thought to be acquired as a byproduct of faulty VDJ recombination in pre-or pro-B cells. 36 We observed that CREBBP mutations occur as an early secondary event in FL, 14 which has been validated in subsequent studies, 12 and we therefore speculate that this may also occur at an early stage of B-cell development. Inactivation of Crebbp was associated with marked reductions in the frequencies of multiple B-cell subsets in both young and adult mice, in line with prior observations that loss of Crebbp with a Cd19-cre resulted in ;50% loss in peripheral B cells.…”
Section: Discussionsupporting
confidence: 75%
“…2 We and others have shown that CREBBP mutations are early events in the clonal evolution of FL and are maintained in the tumor at progression and transformation. 9,10,12,14,23 In addition, we showed that CREBBP point mutations in FL are associated with a marked downregulation of major histocompatibility complex (MHC) class II expression and may therefore drive immune evasion. 14 Other studies have shown that CREBBP mutations in DLBCL may drive disease pathogenesis through the deregulation of BCL6 or TP53 function.…”
Section: Introductionmentioning
confidence: 99%
“…51,53 In our own work, we found that FL cases with subsequent transformation had higher numbers of structural rearrangements as compared with cases experiencing either progression in the absence of transformation, or cases who were event-free for at least 5 years following diagnosis. 24 These findings clearly suggest that genome-wide discovery approaches hold great potential for uncovering genomic properties of rapid transformation.…”
Section: Risk Of Transformation Conferred By Genetic Alterationsmentioning
confidence: 98%
“…[19][20][21][22][23] On the molecular level, transformed FL (TFL) differs from preceding indolent FL by higher numbers of single-nucleotide mutations, small insertions and deletions, copy-number changes, and structural rearrangements. [24][25][26] Transformation occurs via the activation of known or putative oncogenes (MYC, CCND3) and inactivation of known or putative tumor suppressor genes (TP53, CDKN2A/B, B2M). [26][27][28][29][30][31][32][33][34][35] Recent genome-wide studies have contributed to expanding our knowledge on the breadth of genetic alterations that are associated with transformation.…”
Section: The Pathogenesis Of Transformation From Underlying Flmentioning
confidence: 99%
See 1 more Smart Citation